2008
DOI: 10.1007/s11090-008-9129-z
|View full text |Cite
|
Sign up to set email alerts
|

Relating Spectroscopic Measurements in a Plasma Cutting Torch to Cutting Performance

Abstract: The relationship between plasma properties and cutting performance for a plasma arc cutting system was investigated. Plasma properties such as temperature and composition were measured using spectroscopic techniques in a 200 amp oxygen plasma cutting system. In addition to the plasma properties, the symmetry of the cylindrical cutting arc was also quantified. Cutting performance was measured by analyzing the edge quality of sample cuts. The most important measure of edge quality for this study was the angle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…These assumptions are generally accepted by published papers [7,8,[11][12][13][15][16][17][18][19], and they all derived results which are in a good agreement with the experiment. For the nontransferred arc plasma, taking into account the Steenbeck law, arc root position makes 3D necessary.…”
Section: Assumptionsmentioning
confidence: 66%
See 2 more Smart Citations
“…These assumptions are generally accepted by published papers [7,8,[11][12][13][15][16][17][18][19], and they all derived results which are in a good agreement with the experiment. For the nontransferred arc plasma, taking into account the Steenbeck law, arc root position makes 3D necessary.…”
Section: Assumptionsmentioning
confidence: 66%
“…An efficient method to avoid the double arcing is to separate the nozzle into two insulated partitions [17]. The resulting structure is called a ''double nozzle structure'' in the present paper which is different from the dual gas structure in the papers [1,2,10,16,18]. The dual gas structure is composed of a nozzle and a shield cap.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The length and diameter of nozzle are chosen as 2.8 and 2 mm. This torch configuration is widely investigated in the previous studies [7,11,17,23,24]. The parabolic current density of Eq.…”
Section: The Effects Of Arc Currentmentioning
confidence: 99%
“…Using this insert shape that provides for reduced deposition of the high thermionic emissivity material on the nozzle, thereby reducing nozzle wear in the torch. The results of report [6] suggested that the plasma temperature is decreased by heavy deposits of eroded cathode material on nozzle after the large crater forms in cathode, and the cut quality also decreases in case of cathode pit wears. The authors of the reports [7,8] suggested a start-up erosion mechanism by using high-speed camera imaging.…”
Section: Introductionmentioning
confidence: 97%